2012
DOI: 10.1016/j.ygeno.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide analysis reveals association of a FTO gene variant with epigenetic changes

Abstract: Variants of the FTO gene show strong association with obesity, but the mechanisms behind this association remain unclear. We determined the genome wide DNA methylation profile in blood from 47 female preadolescents. We identified sites associated with the genes KARS, TERF2IP, DEXI, MSI1, STON1 and BCAS3 that had a significant differential methylation level in the carriers of the FTO risk allele (rs9939609). In addition, we identified 20 differentially methylated sites associated with obesity. Our findings sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 49 publications
2
95
0
Order By: Relevance
“…Among obese children, differences in DNA methylation, an epigenetic regulatory mechanism, were identified at 5 sites at the FTO gene, variants of which are strongly associated with obesity. 139 Similarly, hypomethylation of DNA at the IL-4 gene promoter and hypermethylation of the IFNγ promoter have been observed in children with atopic asthma. 143 Genome-wide studies have also identified differential methylation of several genes associated with atopic inflammation among asthmatics.…”
Section: Epigenetics Of Obesity-related Asthmamentioning
confidence: 96%
See 1 more Smart Citation
“…Among obese children, differences in DNA methylation, an epigenetic regulatory mechanism, were identified at 5 sites at the FTO gene, variants of which are strongly associated with obesity. 139 Similarly, hypomethylation of DNA at the IL-4 gene promoter and hypermethylation of the IFNγ promoter have been observed in children with atopic asthma. 143 Genome-wide studies have also identified differential methylation of several genes associated with atopic inflammation among asthmatics.…”
Section: Epigenetics Of Obesity-related Asthmamentioning
confidence: 96%
“…Epigenetic differences have been identified in context of both obesity 139,140 and asthma 141,142 compared with healthy controls. Among obese children, differences in DNA methylation, an epigenetic regulatory mechanism, were identified at 5 sites at the FTO gene, variants of which are strongly associated with obesity.…”
Section: Epigenetics Of Obesity-related Asthmamentioning
confidence: 99%
“…Overall, obesity associated DM sites were enriched both in obesity candidate genes 62 and in genes with a wide diversity of other functions, such as immune response 63 , cell differentiation 62 and regulation of transcription 61 . DM sites were also identified in or near genes with no known function related to obesity or adipose tissue functioning.…”
Section: Genome-wide Analyses and Obesitymentioning
confidence: 99%
“…20 Bisulfite conversion of genomic DNA and sample preparation for the platform analysis was performed as described earlier. 21 The BeadChip was read on an Illumina iScan scanner and processed using the GenomeStudio 2009.2 software (Illumina).…”
Section: Dna Methylation Profilingmentioning
confidence: 99%